1184 Operation Note – Are We Documenting Accessibility to The Larynx. (12th October 2021) - Motter, D; Williams, H
Abstract: Introduction: Diagnostic laryngeal procedures are often done under general anaesthesia to aid in assessment and management of laryngeal lesions. Obtaining tissue samples for histology is an extremely important tool used to aid in further surgical planning. Documentation of accessibility to the larynx is paramount to patient care and future surgical planning. We aimed to highlight operative notes for those undergoing diagnostic procedures and assess whether sufficient detail is documented. The Royal College of Surgeons recommends that all operative notes must be comprehensive and "all problems/complications" must be documented for good practice. Method: We carried out a 3-month retrospective data collection on patients who have undergone diagnostic laryngeal procedures at the Royal Glamorgan Hospital. We included microlaryngoscopies, panendoscopies and laser-specific procedures. We accessed the theatre booking system and retrieved the operation notes. Results: During the 3-month period, 33 procedures were undertaken. 52% of the operative notes did not document level of accessibility. 48% of the operative notes included the level of accessibility, highlighting keywords such as "good access", "difficult access" and "difficult access but possible for laser therapy". Conclusions: Documentation of intra-operative findings can aid further surgical management and help prepare the surgeon and theatre staff. It is especially important in patients who have vocal cord lesions that might benefit from laser therapy. We recommend documenting the intubation grade (Malampati Score) and accessibility to the larynx.